EVALUATION AND MEASURE OF ACCURACY OF ICT, CLIA AND NAT FOR THE DETECTION OF HEPATITIS B, C AND HIV IN THE BLOOD DONORS ABSTRACT - Irshad, Romana; Umer Farooq; Ihsan Ullah; Abeera Farooq; Tahir Shah; Adeel Gul (Journal of Ayub Medical College Abbottabad, 2023)
Background: A sensitive and specific donor screening strategy is essential for the prevention of transfusion-transmitted infections (TTI). The study was conducted to ascertain the comparative efficacy of ICT, CLIA and NAT methods. Methods: This cross-sectional analytical study was conducted in Regional Blood Center Abbottabad, Pakistan from 1st April to 25 August 2022. 6233 donors were screened for Hep B, C, and HIV by testing simultaneously with ICT, CLIA and NAT. Results: Active Hep B, C and HIV Infection was present in 0.51%, 0.28% and 0.00048% donors respectively. The sensitivity was found to be higher for HBV and HIV with CLIA as compared to ICT but was equal for HCV with both. whereas specificity was the same with both CLIA and ICT for all three viruses. PPV was higher with ICT for HBV and HCV, but for HIV it was found higher by CLIA. NPV was higher for all three viruses by CLIA as compared to ICT. Conclusion: In case rapid testing devices are used for the initial screening of blood in countries with limited resources, positive cases must be confirmed by CLIA and if possible, then by NAT because of missing cases in the window period and false positive cases.